The risk of epilepsy in children with celiac disease: a population‐based cohort study. (22nd March 2020) - Canova, C.; Ludvigsson, J.; Barbiellini Amidei, C.; Zanier, L.; Zingone, F.
Abstract : Backgroundand purpose: The purpose was to estimate the risk of epilepsy in a cohort of young individuals with celiac disease (CD) compared to that of matched references. Methods: The cohort consisted of 213 635 individuals born during 1989–2011 and residing in Friuli‐Venezia Giulia (Italy). 1215 individuals affected by CD and 6075 reference individuals matched by sex and age were identified. Epilepsy was defined by means of hospital diagnosis or drug prescriptions. Conditional logistic regression was used to estimate the odds ratios (ORs) of having epilepsy amongst individuals with CD, before CD diagnosis and in the entire period, compared with those of their matched references. Cox regression was used to calculate the hazard ratios for epilepsy diagnosed after CD diagnosis. Different definitions of epilepsy were used for sensitivity analyses. Results: Thirty‐one (2.6%) individuals with CD and 78 (1.3%) reference individuals had epilepsy [adjusted OR 2.03; 95% confidence interval (CI) 1.33–3.10]. The risk of epilepsy was increased prior to CD (adjusted OR 2.29; 95% CI 1.33–3.94), with similar estimates after CD diagnosis (adjusted hazard ratio 1.96; 95% CI 0.95–4.02). The increased risk of epilepsy was not explained by a peak in epilepsy diagnosis just around CD diagnosis. Sex stratification found a significantly higher risk of epilepsy amongst female individuals with CD. Sensitivity analyses confirmed the positive association between CD and epilepsy. Conclusion: Children and youths with CD were at increased risk of epilepsy. Patients with epilepsy without a clear etiology should be screened for CD since an early diagnosis and treatment might improve the response to antiepileptic therapies.